Maternal high-intensity interval training as a suitable approach for offspring’s heart protection in rat: evidence from oxidative stress and mitochondrial genes - Mohammadkhani, Reihaneh; Komaki, Alireza; Karimi, Seyed Asaad; Behzad, Mahdi; Heidarisasan, Shirin; Salehi, Iraj (Frontiers in Physiology, 2023)
Considerable scientific evidence suggests that the intrauterine environment plays a crucial role in determining the long-term health of offspring. The present study aims to investigate the effects of high-intensity interval training in maternal rats before and during pregnancy on the antioxidant status, mitochondrial gene expression, and anxiety-like behavior of their offspring. A total of thirty-two female rats were assigned to four maternal groups based on the timing of exercise: before pregnancy, before and during pregnancy, during pregnancy, and sedentary. The female and male offspring were allocated to groups that matched their mothers’ exercise regimen. Anxiety-like behavior in the offspring was evaluated using the open-field and elevated plus-maze tests. Our findings indicate that maternal HIIT does not have any detrimental effect on the anxiety-related behavior of offspring. Also, maternal exercise before and during pregnancy could improve the general activity of the offspring. Furthermore, our results demonstrate that female offspring exhibit more locomotion activity than males. Besides, maternal HIIT leads to a reduction in the levels of TOS and MDA, while TAC levels increase, and significantly upregulate the gene expression of PGC1-α, NFR1, and NRF2 in both sexes in the heart. Therefore, our study suggests that maternal HIIT is a beneficial maternal behavior and serves as a cardioprotective agent to enhance the health of the next generations.